Efecto de diferentes dosis de biol y frecuencia de corte sobre las características agronómicas del pasto (Pennisetum sp.) maralfalfa en Iquitos - Loayza Gatica, Miguel Angel (2014)
The Zungarococha Farm, entitled "Effect of Different Doses of Biol and Cutting Frequencies on the Agronomic Characteristics of Pasture (Pennisetum sp.), Maralfalfa in Iquitos.” The evaluations were carried out at the 8th and 10th week after starting the research work (sowing) with plots of 1.2 m x 10 m (12 m2) and an experimental area of 866.4 m2. With a Random Complete Block Design (D.B.C.A), with a 2 x 2 factorial arrangement with four treatments and four repetitions, the treatments under study were classified according to factors, such as: Factor A (Biol Dose), where there was three doses of Biol with 20% and 40%, then we have Factor B (cutting frequency), where there was a frequency of cuts in the 8th week and 10th week, opening the way to the treatments that were: T1 (A1B1), T2 (A2B1), T3 (A2B1) and T4 (A2B2), obtaining the following results: the results of the A2B2 treatment (40% biol with a cut-off frequency at 10 weeks), at the 10th week after starting work research (sowing), the following is concluded. A plant height performance of 1.93m was achieved. Yields of green matter and dry matter (kg/m2) of 6.56 kg/m2 and 1.58 kg/m2 respectively were achieved. A plant coverage yield (%) of 93.75% was achieved. A yield of kg/ha of green matter of 65625 kg/ha was achieved.